Thinking counterfactually-how controllability affects the 'undoing' of causes and enablers - Egan, Suzanne, M.; Frosh, Caren A.; Handcock, Emily N.
Previous research on counterfactual thoughts about prevention suggests that people tend to focus on enabling rather than causing agents. However, research has also demonstrated that people have a preference for mutating controllable events. We explore whether counterfactual thinking about enablers is distinct from ?undoing? controllable events. We presented participants with scenarios in which a cause and an enabler contribute to a negative outcome. Participants were randomly assigned to one of four groups in which we systematically manipulated the controllability of the cause and the enabler. Participants generated counterfactuals which focused on the cause or the enabler and completed blame ratings for the cause and the enabler. The results indicate that participants had a preference for mutating the enabling relation, apart from in one condition where the cause was controllable and the enabler was uncontrollable. Participants tended to assign more blame to the cause than the enabler, regardless of controllability. The findings are discussed in the context of previous research on causal and counterfactual thinking.